Impact of gabion sill on scouring depth downstream grade control structures - Mohammad Bagherzadeh; Mirali Mohammadi (Results in Engineering, 2025)
Grade control structures (GCS) stabilize riverbeds and reduce sediment movement, but downstream scour threatens their stability. This experimental research investigates the effects of gabion sills (GSs) on scour at three relative spacings (Lg/h = 1, 1.5, & 2) under five discharges and three tailwater depths (TwDs) (freely=y′t, 1.5y′t, & 2y′t). A series of experiments conducted in an 18 m-long, 0.3 m-wide tilting flume with a discharge range of 7–13 L/s. The observations demonstrated that the placement of gabions significantly accelerated the bed stabilization process and effectively reduced both the depth and length of the scour hole. The results establish that positioning the GS at a relative spacing of Lg/h = 1 reduces the scouring length and depth by an average of 51% and 44%, respectively, compared to the GCS without a GS under free TwDs conditions. For a case of Lg/h = 1.5, those reductions were 44% and 49%, respectively, while for the case of Lg/h = 2, they were 36% and 7%, correspondingly. The Lg/h = 1 configuration is recommended for controlling scour length, while Lg/h = 1.5 has the most effective among cases in reducing scour depth at high discharge. The findings indicated that an increasing TwD contributes to reducing scouring dimensions. Specifically, in the absence of GS, increasing TwD to 2y′t led to an average reduction of 19% in scour length and 25% in scour depth. A comparison of TwD effects among different GCS models with GS showed that increasing TwD to 2y′t in the Lg/h = 2 GS configuration was the most effective, achieving a 30% reduction in scour depth.